Access to and Quality of Primary Healthcare: a Multi-Country Qualitative Case Study in West and East Africa - Ameh, Soter; Akeem, Bolarinwa Oladimeji; Ochimana, Caleb; Oluwasanu, Abayomi Olabayo; Mohamed, Shukri F; Okello, Samson; Muhihi, Alfa; Danaei, Goodarz (Research square, 2020)
Background: Universal health coverage is one of the Sustainable Development Goal targets known to improve population health and reduce financial burden. There is little qualitative data on access to and quality of primary healthcare in West and East Africa. We elicited in-depth viewpoints of healthcare users and providers, and other stakeholders regarding access to and quality of healthcare. Methods: A qualitative case study was conducted in four communities in Nigeria and one community each in Kenya, Uganda and Tanzania in 2018. Purposive sampling was used to recruit 155 participants for 24 focus group discussions, 24 in-depth interviews, and 12 key informant interviews. The conceptual framework in this study combined elements of the Health Belief Model, Health Care Utilisation Model, four ‘As’ of access to care, and pathway model to better understand health-seeking behaviours of the study participants. The data were analysed with MAXQDA 2018 qualitative software to identify three themes identified a priori and one emerging theme. Results: Access to primary healthcare in the seven communities was limited. Quality of care was perceived to be unacceptable in public facilities whereas cost of care was unaffordable in private facilities. Patients and health providers and stakeholders highlighted shortage of equipment, frequent drug stock-outs and long waiting times as major issues, but had varying opinions on satisfaction with care. Use of herbal medicines and other traditional treatments delayed or deterred seeking modern healthcare in Nigerian sites. Conclusions: There was a substantial gap in primary healthcare coverage and quality in the selected communities in rural and urban East and West Africa. Alternative models of healthcare delivery should be used to all this gap and facilitate achieving universal health coverage.
Keywords: Access; Quality; Primary healthcare; universal health coverage; Health-seeking behaviour; Social entrepreneurship; Nigeria; Kenya; Uganda; Tanzania.